Evaluation of a plane-parallel ionization chamber for low-energy radiotherapy beams (Brazilian Journal of Radiation Sciences (BJRS), 2015)
A plane-parallel ionization chamber, with a sensitive volume of 6.3 cm3, developed at the Calibration Laboratory of IPEN (LCI), was utilized to verify the possibility of its application in low-energy X-ray beam qualities for radiotherapy (T-qualities). This homemade ion chamber was manufactured using polymethyl methacrylate (PMMA) coated with graphite, and co-axial cables. In order to evaluate the performance of this ionization chamber, some characterization tests were performed: short- and medium-term stability, leakage current, saturation, ion collection efficiency, polarity effect and linearity of response. The maximum value obtained in the short-term stability test was 0.2%, in accordance with the limit value of 0.3% provided by the IEC 60731 standard.  The saturation curve was obtained varying the applied voltage from -400 V to +400 V, in steps of 50 V, using the charge collecting time of 20 s. From the saturation curve two other characteristics were analyzed: the polarity effect and the ion collection efficiency, with results within the international recommendations. The leakage current of the ionization chamber was measured in time intervals of 20 minutes, before and after its irradiations, and all the results obtained were in agreement with the IEC 60731 standard. The linearity of response was verified utilizing the T-50(b) radiation quality, and the ionization chamber was exposed to different air kerma rates. The response of the ionization chamber presented a linear behavior. Therefore, all results were considered satisfactory, within international recommendations, indicating that this homemade ionization chamber presents potential routine use in dosimetry of low-energy radiotherapy beams.